Preparation and application of chain-shaped phosphomolybdic acid-based nickel coordination polymer crystal

The preparation of chain phosphorus-molybdenum polyacid-based nickel coordination polymers by one-step hydrothermal synthesis method has solved the problem of poor conductivity and stability of polyacid polymers in acidic solutions, and achieved efficient electrocatalytic nitrate in the field of synthesis of ammonia Improved restore performance.

CN119264449APending Publication Date: 2025-01-07HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411387555.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-04
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Polyacid polymers, as electrocatalytic nitrate reduction catalysts, have poor conductivity and stability in acidic solutions, limiting their application in the field of synthesis of ammonia.

Method used

By one-step hydrothermal synthesis, 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10) o-diazaphenyl, sodium molybdate, nickel chloride A chain-shaped phosphorus-molybdenum polyacid-based nickel coordination polymer was prepared to form a one-dimensional long chain structure rich in nickel atoms, which improved electron transport capability and stability.

Benefits of technology

The polymer significantly improves the electrocatalytic nitrate reduction performance in an acidic environment, maintains stable ammonia production and Faraday efficiency, demonstrating excellent stability and high catalytic activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005071371070000042
    Figure BDA0005071371070000042
  • Figure BDA0005071371070000051
    Figure BDA0005071371070000051
  • Figure BDA0005071371070000061
    Figure BDA0005071371070000061
Patent Text Reader

Abstract

The invention relates to preparation and application of a chain-shaped phosphomolybdic acid-based nickel coordination polymer crystal. The invention aims to solve the problems of poor conductivity and stability of some polyacid polymers as an electrocatalytic nitrate reduction catalyst in an acid solution, and provides a preparation method of a nitrate synthesis ammonia electrocatalytic material capable of improving the internal electron transmission capability. The chemical formula of the chain-shaped phosphorus molybdenum polyacid-based nickel coordination polymer crystal is (HNCP) 2 [Ni (H2O) 3] 2 [NiMo12 (H2PO4) 6 (PO4) 2 (OH) 6O24], and the HNCP is 2-(4-(4-carboxyl phenyl) phenyl) imidazo (4, 5-f) (1, 10) phenanthroline. The synthesis method comprises the following steps: adding sodium molybdate, nickel chloride and HNCP into ethanol and distilled water, uniformly stirring, adjusting the pH value, and reacting for 5 days at the temperature of 180 DEG C. The highest ammonia yield and Faraday efficiency of an electrocatalytic material prepared from the obtained polymer in a low-concentration acidic electrolytic solution are 4.88 mg h <-1 > mg <-1 > cat and 72.1% respectively. And a technical route is provided for constructing a multi-acid-group nitrate reduction catalyst suitable for an acidic medium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation and application of chain-like phosphomolybdic acid-based nickel coordination polymer crystal. Background Art

[0002] Ammonia is a chemical raw material for the production of agricultural fertilizers and industrial chemicals, and is also an important energy storage medium and carbon-free energy carrier. At present, ammonia is mainly produced by the energy-intensive Hubble process, which requires high temperature and high pressure conditions and consumes a lot of energy. Under ambient conditions, the electrocatalytic nitrate reduction reaction has attracted more and more attention due to its safety, low cost and environmental friendliness, which makes it show good application prospects in the field of synthetic ammonia.

[0003] Polyoxometalates (POMs), also known as polyoxometalates, are a class of nanometallic oxygen cluster compounds with clear structure and adjustable composition. They have the characteristics of diverse composition, reversible redox property, and high thermal stability. 31 ] 12- , abbreviated as {P4Mo6}, has a high negative charge number, small steric hindrance and abundant coordinated oxygen atoms on the surface. However, the strong water solubility and poor conductivity of polyacids inhibit their application in the field of electrocatalytic nitrate reduction.

[0004] Polyacid-based metal organic coordination polymers are a class of crystalline materials with rich long-range ordered crystal structures, and have clear composition and spatial structure, excellent redox properties and electron transfer ability. Among them, polyacids and metal ions are connected to each other by chemical bonds, which can form an electron pathway that is easier for electron transfer, which helps to improve the electrochemical performance of the material. Therefore, {P4Mo6} is used as a structural unit, metal organic complexes are introduced, and a polyacid-based metal organic framework structure is constructed by inducing metal cations to coordinate with {P4Mo6}. At the same time, {P4Mo6} can also serve as an electron reservoir to directly provide electrons to metal ions, realize the rapid activation of metal ion catalytic centers, and improve catalytic performance. Based on the good application prospects of polyacid-based metal organic coordination polymers, we studied and prepared a new one-dimensional chain phosphomolybdic polyacid-based nickel coordination polymer with electrocatalytic nitrate reduction performance that has not been reported in the literature. Summary of the invention

[0005] The purpose of the present invention is to solve the problem that some polyacid polymers have poor conductivity and stability in acidic solutions as electrocatalytic nitrate reduction catalysts. In order to improve its ammonia synthesis performance, the present invention provides a preparation method and application of a phosphorus molybdenum polyacid-based nickel coordination polymer with a one-dimensional long chain structure.

[0006] In order to solve the above technical problems, the present invention is achieved through the following technical solutions:

[0007] 1. Preparing a reaction solution with a pH value of 1.3 to 1.5: adding sodium molybdate, nickel chloride and 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline to ethanol and distilled water and stirring evenly, and then adjusting the pH value of the suspension to 1.3 to 1.5 to obtain a reaction solution with a pH value of 1.3 to 1.5;

[0008] The molar ratio of sodium molybdate to nickel chloride in step 1 is 1:0.20;

[0009] The molar ratio of sodium molybdate to 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline in step 1 is 1:0.05;

[0010] The volume ratio of the amount of sodium molybdate described in step 1 to ethanol and distilled water is: 0.62mmol:1mL:4mL;

[0011] 2. The reaction solution prepared in step 1 was transferred to a polytetrafluoroethylene reactor, and then reacted at a temperature of 180°C for 5 days. The reaction solution was cooled to room temperature and then washed to obtain yellow-brown cicada wing-shaped crystals, i.e., chain-like phosphomolybdic acid-based nickel coordination polymer, the chemical formula of which is (HNCP)2[Ni(H2O)3]2[NiMo 12 (H2PO4)6(PO4)2(OH)6O 24 ], where HNCP is 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline; the crystal appearance is yellow-brown cicada wing-shaped; the crystal system is triclinic; the space group is Pī; the unit cell parameters are c=14.5618(9) α=63°, β=83°, γ=85°,

[0012] 3. Preparation of an electrocatalytic nitrate reduction electrode of a chain-type phosphomolybdic polyacid-based nickel coordination polymer: Grind 20 mg of the chain-type phosphomolybdic polyacid-based nickel coordination polymer and 20 mg of acetylene black evenly, take 3 mg of the ground sample and add it to 125 μL of isopropanol, 10 μL of Nafion solution and 365 μL of water, and ultrasonicate for 2 hours to obtain a uniformly dispersed mixed solution, take 10 μL of the mixed solution and drop it on the pretreated carbon cloth, and after standing at room temperature for 10 hours, a working electrode modified with a chain-type phosphomolybdic polyacid-based nickel coordination polymer was obtained.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] 1. The present invention successfully prepared a polyacid-based metal organic coordination polymer for the first time by using 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline organic ligand, sodium molybdate and nickel chloride through a one-step hydrothermal synthesis method. Single crystal X-ray diffraction results show that the crystalline material prepared by the present invention is a chain-like phosphorus molybdenum polyacid-based nickel coordination polymer.

[0015] The polymer molecules are rich in nickel atoms, which coordinate with the oxygen atoms of polyacids and water molecules through nickel-oxygen bonds, and connect with the nitrogen of organic ligands to form a one-dimensional molecular chain structure. Therefore, the polymer forms a stable one-dimensional chain structure through the interaction of a large number of chemical bonds.

[0016] 2. A chain-like phosphomolybdic acid-based nickel coordination polymer prepared in this embodiment is used as an electrocatalytic nitrate reduction catalyst. The ammonia production at -0.5 V vs. RHE is 4.88 mg h -1 mg -1 cat. The results show that this one-dimensional long chain structure improves the electron transfer capacity, and this one-dimensional structural feature is conducive to the improvement of the electrocatalytic nitrate reduction performance in an acidic environment. Therefore, this method provides a research model for the synthesis of ammonia from nitrates by polyacid-based metal organic coordination polymers.

[0017] The working electrode was tested for nitrate reduction at voltages of -0.3, -0.4, -0.5, -0.6, -0.7 and -0.8 V vs. RHE, as shown in Figure 2. Figure 7 As shown in FIG. 1 , in a 0.1M NaNO3 / 0.05M H2SO4 solution, at -0.7V (vs. RHE), the maximum Faraday efficiency is 72.1%. A 12h stability test was performed in a 0.1M NaNO3 / 0.05M H2SO4 electrolyte. Figure 8 As shown, after 12 h of continuous electrolysis, the current density, ammonia production and Faraday efficiency remained stable, proving that the polymer has excellent stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is an example - a diagram of the basic structural unit of a chain-like phosphomolybdic acid-based nickel coordination polymer.

[0019] Figure 2 This is an example - a schematic diagram of the structural connection of a chain-like phosphomolybdic acid-based nickel coordination polymer.

[0020] Figure 3 This is an example - a schematic diagram of the three-dimensional stacking of chain-like phosphomolybdic acid-based nickel coordination polymer.

[0021] Figure 4This is the infrared spectrum of the embodiment - chain-like phosphomolybdic acid-based nickel coordination polymer.

[0022] Figure 5 This is the powder X-ray diffraction pattern of the chain-like phosphomolybdic acid-based nickel coordination polymer of Example.

[0023] Figure 6 This is an example - a chain-like nickel-phosphomolybdic acid-based coordination polymer is used as a working electrode, and the ultraviolet-visible light absorption spectrum at different voltages in 0.1MNaNO3 / 0.05M H2SO4 electrolyte.

[0024] Figure 7 For example, a chain-like phosphomolybdic acid-based nickel coordination polymer is used as a working electrode, and the ammonia production and Faraday efficiency are shown when the voltages are -0.3, -0.4, -0.5, -0.6, -0.7 and -0.8 V vs. RHE in 0.1 M NaNO3 / 0.05 M H2SO4 electrolyte.

[0025] Figure 8 For example, a chain-like phosphomolybdic acid-based nickel coordination polymer is used as a working electrode. When the voltage is -0.5V vs. RHE in 0.1MNaNO3 / 0.05M H2SO4 electrolyte, the time-current curve of 12 hours and the ammonia production and Faraday efficiency of 12 cycle reactions are continuously tested. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0027] Specific implementation method 1: This implementation method describes a phosphomolybdic acid-based nickel coordination polymer with a one-dimensional long chain structure, and the molecular formula of the polymer is C 40 H 24 Mo 12 N8Ni5O 88P8, its basic structural unit contains three Ni metal ions, one {P4Mo6}, and one HNPC; the nickel ion has three coordination environments, Ni1 is a six-coordination mode, composed of two polyacids each providing three bridging oxygens in Mo-O-Mo; Ni2 is also a six-coordination mode, composed of two N in the ligand, three coordinated water molecules and oxygen atoms of the polyacid; the third Ni3 is also a six-coordination mode, composed of a PO terminal oxygen in a polyacid and two PO terminal oxygens in another polyacid, as well as oxygen atoms of three coordinated water molecules. At the same time, Ni1 and Ni3 serve as connection points to extend the polyacid to form a one-dimensional long chain structure. Multiple long chains are stacked through electrostatic forces and hydrogen bonds to form a three-dimensional stacking structure.

[0028] Specific implementation method 2: The preparation method of a phosphomolybdic acid-based nickel coordination polymer with a one-dimensional long chain structure in this implementation method is completed by the following steps:

[0029] 1. Prepare a reaction solution with a pH value of 1.3 to 1.5: add 1.5 g of sodium molybdate, 0.3 g of nickel chloride and 0.1 g of 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline to ethanol and distilled water and stir evenly, then adjust the pH value of the suspension to 1.3 to 1.5 to obtain a reaction solution with a pH value of 1.3 to 1.5;

[0030] The molar ratio of sodium molybdate to nickel chloride in step 1 is 1:0.20;

[0031] The molar ratio of sodium molybdate to 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline in step 1 is 1:0.05;

[0032] The volume ratio of the amount of sodium molybdate described in step 1 to ethanol and distilled water is: 0.62mmol:1mL:4mL;

[0033] 2. Preparation of chain-like phosphomolybdic acid-based nickel coordination polymer: The reaction solution prepared in step 1 is transferred to a polytetrafluoroethylene reactor, and then reacted at a temperature of 180°C for 5 days. The reaction solution temperature is lowered to room temperature and then washed to obtain yellow-brown cicada wing-shaped crystals, i.e., chain-like phosphomolybdic acid-based nickel coordination polymer crystalline materials. The chemical formulas of the polymers are (HNCP)2[Ni(H2O)3]2[NiMo 12 (H2PO4)6(PO4)2(OH)6O 24 ], where HNCP is 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline; the crystal appearance is yellow-brown cicada wing-shaped; the crystal system is triclinic; the space group is Pī; the unit cell parameters are α=63°, β=83°, γ=85°,

[0034] 3. Preparation of an electrocatalytic nitrate reduction electrode of a chain-type phosphomolybdic polyacid-based nickel coordination polymer: Grind 20 mg of the chain-type phosphomolybdic polyacid-based nickel coordination polymer and 20 mg of acetylene black evenly, take 3 mg of the ground sample and add it to 125 μL of isopropanol, 10 μL of Nafion solution and 365 μL of water, and ultrasonicate for 2 hours to obtain a uniformly dispersed mixed solution. Take 10 μL of the mixed solution and drop it on the pretreated carbon cloth. After standing at room temperature for 10 hours, the working electrode modified with the chain-type phosphomolybdic polyacid-based nickel coordination polymer was obtained, which was used to test the nitrate reduction performance.

[0035] The carbon cloth described in step three needs to be pretreated. The specific process is: first, soak it in acetone solution for 30 minutes, then ultrasonically soak it in anhydrous ethanol and deionized water for 3 times, each ultrasonic time is 30 minutes, and finally, completely immerse the carbon cloth in concentrated nitric acid, put it in a reactor, and react it at 120°C for 2 hours. After cooling to room temperature, wash it with deionized water until the pH is neutral, and then the carbon cloth can be used. At the same time, the electrochemical test selects a three-electrode system, with the modified glassy carbon electrode as the working electrode, the silver / silver chloride electrode as the reference electrode, and platinum as the counter electrode.

[0036] Specific implementation method three: Specific implementation method two step one of the preparation method of the chain phosphomolybdic acid-based nickel coordination polymer, the molar ratio of sodium molybdate, nickel chloride, and 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline is 1:0.20:0.05.

[0037] Specific embodiment 4: This embodiment differs from specific embodiment 2 in that the metal nickel salt in step 1 is nickel acetate, nickel nitrate or nickel sulfate. The rest is the same as specific embodiments 1 to 3.

[0038] Specific implementation method five: Specific implementation method two step one of the preparation method of the chain-like phosphomolybdic acid-based nickel coordination polymer, the volume ratio of the amount of sodium molybdate to ethanol and distilled water is: 0.62mmol:1mL:4mL.

[0039] Specific embodiment 6: The difference between this embodiment and specific embodiment 2 is that the pH value of the reaction solution is adjusted to 1.3-1.5 in step 1 by using H3PO4 solution and NaOH solution with molar concentrations of 1 mol / L. The other steps are the same as those of specific embodiments 1 to 5.

[0040] Specific embodiment 7: The difference between this embodiment and specific embodiment 2 is that the reaction temperature in step 2 is 180° C. and the reaction time is 5 days. The other steps are the same as specific embodiments 1 to 6.

[0041] Specific embodiment eight: the mass of the prepared phosphomolybdic acid coordination polymer, acetylene black, and the volume ratio of isopropanol to distilled water described in step three of specific embodiment two are 1.5 mg: 1.5 mg: 0.125 mL: 0.365 mL.

[0042] The following examples are used to verify the beneficial effects of the present invention:

[0043] Embodiment - the preparation method of chain-like phosphomolybdic acid-based nickel coordination polymer is achieved by the following steps:

[0044] 1. Prepare a reaction solution with a pH value of 1.3: evenly disperse 6.20 mmol of sodium molybdate, 1.26 mmol of nickel chloride and 0.29 mmol of 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline in a mixed solution of 10 mL of ethanol and 40 mL of distilled water, and then adjust the pH value of the reaction solution to 1.3 using 1 mol / L H3PO4 solution and 1 mol / L NaOH solution to obtain a reaction solution with a pH value of 1.3.

[0045] The molar ratio of sodium molybdate to nickel chloride in step 1 is 1:0.20;

[0046] The molar ratio of sodium molybdate to 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline in step 1 is 1:0.05;

[0047] The volume ratio of the amount of sodium molybdate described in step 1 to ethanol and distilled water is: 0.62mmol:1mL:4mL;

[0048] 2. The prepared reaction solution with a pH value of 1.3 was transferred to an 80 mL polytetrafluoroethylene reactor, and then reacted at a temperature of 180°C for 5 days. The reaction solution was cooled to room temperature and then washed to obtain yellow-brown cicada wing-shaped crystals, which are phosphomolybdic acid-based nickel coordination polymers with a one-dimensional long-chain structure.

[0049] (I) Structural determination of the chain-like phosphomolybdic acid-based nickel coordination polymer prepared in Example 1:

[0050] Conclusion ① X-ray crystallography parameters: see Table 1.

[0051] Table 1 Crystallographic parameters of materials

[0052]

[0053]

[0054] a R1=∑║F o │─│F c ║ / ∑│F o │. b wR2={∑[w(F o 2 ─F c 2 ) 2 ] / ∑[w(F o 2 ) 2 ]} 1 / 2

[0055] Conclusion②X-ray crystal structure description: X-ray single crystal diffraction analysis shows that

[0056] The chain-like phosphomolybdic acid-based nickel coordination polymer is a triclinic crystal system. Space group. The unit cell parameters are α=63°, β=83°, γ=85°, like Figure 1 As shown, the polymer includes three Ni metal ions, one {P4Mo6}, and one HNPC. There are three chemical states of Ni atoms. Ni1 is a six-coordinate mode, composed of two polyacids each providing three bridging oxygens in Mo-O-Mo; Ni2 is also a six-coordinate mode, composed of two N in the ligand, three coordinated water molecules and oxygen atoms of the polyacid; the third Ni3 is also a six-coordinate mode, composed of a PO terminal oxygen in a polyacid and two PO terminal oxygens in another polyacid, as well as oxygen atoms of three coordinated water molecules. At the same time, Ni1 and Ni3 serve as connection points to extend the polyacid to form a one-dimensional long chain structure (such as Figure 2 As shown). Multiple long chains are stacked through electrostatic forces and hydrogen bonds to form a three-dimensional stacking structure (as shown Figure 3 shown).

[0057] Figure 1 This is an example - a diagram of the basic structural unit of a chain-like phosphomolybdic acid-based nickel coordination polymer.

[0058] Figure 2 This is an example - a schematic diagram of the structural connection of a chain-like phosphomolybdic acid-based nickel coordination polymer.

[0059] Figure 3 This is an example - a schematic diagram of the three-dimensional stacking of chain-like phosphomolybdic acid-based nickel coordination polymer.

[0060] (ii) Example - chain phosphomolybdic acid-based nickel coordination polymer (HNCP) 2[Ni(H2O)3]2[NiMo 12 (H2PO4)6(PO4)2(OH)6O 24 ] to perform infrared spectroscopy characterization to obtain the infrared spectrum of the phosphomolybdic acid-based nickel coordination polymer. Figure 4 As shown, at 1073, 976, 813 and 733 cm -1 The characteristic peaks are attributed to ν(PO), ν(Mo=Ot), ν(Mo-Ob-Mo) and ν(Mo-Oc-Mo) stretching vibrations; the vibration peaks are between 1100 and 1690 cm -1 The range is attributed to organic ligands, at 3444cm -1 The peak at 1023cm is attributed to the stretching vibration of water molecules in the compound. -1 The characteristic peak at is attributed to the stretching vibration of ν(Ni-N) in the crystal structure.

[0061] Figure 4 This is the infrared spectrum of the embodiment - chain-like phosphomolybdic acid-based nickel coordination polymer.

[0062] (III) Example - chain-like molybdenum phosphide-based nickel coordination polymer (HNCP) 2[Ni(H2O)3]2[NiMo 12 (H2PO4)6(PO4)2(OH)6O 24 ] to perform powder X-ray diffraction measurement to obtain the powder X-ray diffraction spectrum of the phosphomolybdic acid-based nickel coordination polymer. Figure 5 As shown, the peak positions of the experimentally measured spectrum and the spectrum obtained by crystal simulation are consistent. It can be determined that the crystal structure obtained by the experiment is the structure analyzed by the software, and the purity of the crystal is very high.

[0063] Figure 5 This is the powder X-ray diffraction pattern of the chain-like phosphomolybdic acid-based nickel coordination polymer of Example.

[0064] (IV) Example - chain phosphomolybdic acid-based nickel coordination polymer (HNCP) 2[Ni(H2O)3]2[NiMo 12 (H2PO4)6(PO4)2(OH)6O 24 ] to test the electrochemical performance. A three-electrode system was used, with a glassy carbon electrode as the working electrode, a silver / silver chloride electrode as the reference electrode, and platinum as the counter electrode. The electrochemical time-current curve of the polymer was tested at different voltages in a 0.1M NaNO3 / 0.05M H2SO4 electrolyte. After measuring for 1 hour, 10mL of the electrolyte in the anode electrolytic cell was taken for color development and tested using a UV spectrophotometer. Figure 6As shown in the figure, at -0.7V vs.RHE, the chain-like phosphomolybdic acid-based nickel coordination polymer has a higher absorbance, indicating that the complex has good electrocatalytic nitrate reduction properties at -0.7V vs.RHE voltage. The working electrode was tested for nitrate reduction at voltages of -0.3, -0.4, -0.5, -0.6, -0.7 and -0.8V vs.RHE, as shown in the figure. Figure 7 As shown in Figure 2, the maximum Faradaic efficiency of the polymer is 72.1% at -0.5 V vs. RHE, and the maximum ammonia production is 4.88 mg h at -0.7 V vs. RHE. -1 mg -1 cat. The stability test was carried out in 0.1M NaNO3 / 0.05M H2SO4 electrolyte for 12h. Figure 8 As shown, after 12 h of continuous electrolysis, the current density, ammonia production and Faraday efficiency remained stable, proving that the polymer has excellent stability.

[0065] Figure 6 This is an example - a chain-like nickel-phosphomolybdic acid-based coordination polymer is used as a working electrode, and the ultraviolet-visible light absorption spectrum at different voltages in 0.1MNaNO3 / 0.05M H2SO4 electrolyte.

[0066] Figure 7 For example, a chain-like phosphomolybdic acid-based nickel coordination polymer is used as a working electrode, and the ammonia production and Faraday efficiency are shown when the voltages are -0.3, -0.4, -0.5, -0.6, -0.7 and -0.8 V vs. RHE in 0.1 M NaNO3 / 0.05 M H2SO4 electrolyte.

[0067] Figure 8 For example, a chain-like phosphomolybdic acid-based nickel coordination polymer is used as a working electrode. When the voltage is -0.5V vs. RHE in 0.1MNaNO3 / 0.05M H2SO4 electrolyte, the time-current curve of 12 hours and the ammonia production and Faraday efficiency of 12 cycle reactions are continuously tested.

[0068] In summary: a chain phosphomolybdic acid-based nickel coordination polymer prepared in Example 1 is used for the electrocatalytic nitrate reduction reaction. The polymer has high catalytic activity for nitrate, and has excellent conductivity and stability. It is an electrocatalytic material with excellent performance and shows potential application value in the field of synthetic ammonia.

Claims

1. A chain-like nickel coordination polymer crystal based on molybdenum phosphide, the chemical formula of which is (HNCP)2[Ni(H2O)3]2[NiMo 12 (H2PO4)6(PO4)2(OH)6O 24 ], where HNCP is 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline; the crystal appearance is yellow-brown cicada wing-shaped; the crystal system is triclinic; the space group is Pī; the unit cell parameters are α=63°, β=83°, γ=85°, 2. A chain-like phosphomolybdic acid-based nickel coordination polymer, characterized in that Different from the structure of other types of phosphomolybdic acid polymers. There are three Ni metal ions, one {P4Mo6}, and one HNPC in its basic structural unit. There are three chemical states of Ni atoms. Ni1 is a six-coordinate mode, composed of two polyacids each providing three bridging oxygens in Mo-O-Mo; Ni2 is also a six-coordinate mode, composed of two N in the ligand, three coordinated water molecules and oxygen atoms of the polyacid; the third Ni3 is also a six-coordinate mode, composed of a PO terminal oxygen in a polyacid and two PO terminal oxygens in another polyacid, as well as oxygen atoms of three coordinated water molecules. At the same time, Ni1 and Ni3 serve as connection points to extend the polyacid to form a one-dimensional long chain structure. Multiple long chains are stacked through electrostatic forces and hydrogen bonds to form a three-dimensional stacking structure.

3. The preparation method of the phosphomolybdic acid-based nickel coordination polymer having a one-dimensional long chain structure is completed by the following steps:

1. Prepare a reaction solution with a pH value of 1.3 to 1.5: add 1.5 g of sodium molybdate, 0.3 g of nickel chloride and 0.1 g of 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline to ethanol and distilled water and stir evenly, then adjust the pH value of the suspension to 1.3 to 1.5 to obtain a reaction solution with a pH value of 1.3 to 1.

5. The molar ratio of sodium molybdate to nickel chloride in step 1 is 1:0.20; The molar ratio of sodium molybdate to 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline in step 1 is 1:0.05; The volume ratio of the amount of sodium molybdate described in step 1 to ethanol and distilled water is: 0.62mmol:1mL:4mL; 2. Preparation of a phosphomolybdic acid-based nickel coordination polymer with a one-dimensional long-chain structure: The reaction solution prepared in step 1 is transferred to a polytetrafluoroethylene reactor, and then reacted at a temperature of 180°C for 5 days. The reaction solution temperature is lowered to room temperature and then washed to obtain yellow-brown cicada wing-shaped crystals, i.e., a phosphomolybdic acid-based nickel coordination polymer with a one-dimensional long-chain structure. The polymer chemical formula described in step 2 is (HNCP)2[Ni(H2O)3]2[NiMo 12 (H2PO4)6(PO4)2(OH)6O 24 ], where HNCP is 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline; the crystal appearance is yellow-brown cicada wing-shaped; the crystal system is triclinic; the space group is Pī; the unit cell parameters are α=63°, β=83°, γ=85°, 4. The method for preparing a chain-like phosphomolybdic acid-based nickel coordination polymer according to claim 3, characterized in that The nickel chloride described in step 1 can be replaced by nickel acetate, nickel nitrate or nickel sulfate.

5. The method for preparing a chain-like phosphomolybdic acid-based nickel coordination polymer according to claim 3, characterized in that The molar ratio of sodium molybdate, nickel chloride, and 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline described in step 1 is 1:0.20:0.

05. Meanwhile, the structural formula of the organic ligand 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline described in step 1 is 6. The method for synthesizing a chain-like phosphomolybdic acid-based nickel coordination polymer according to claim 3, characterized in that The volume ratio of the amount of sodium molybdate described in step 1 to ethanol and distilled water is: 6.20mmol:10mL:40mL.

7. The method for synthesizing a chain-like phosphomolybdic acid-based nickel coordination polymer according to claim 3, characterized in that In step 1, the pH value of the reaction solution is adjusted to 1.3-1.5 using a H3PO4 solution with a molar concentration of 1 mol / L and a NaOH solution with a molar concentration of 1 mol / L.

8. The method for preparing a chain-like phosphomolybdic acid-based nickel coordination polymer according to claim 3, characterized in that The reaction temperature in step 2 is 180° C. and the reaction time is 5 days.

9. Preparation of an electrocatalytic nitrate reduction electrode of a chain-type phosphomolybdic polyacid-based nickel coordination polymer: Grind 20 mg of one-dimensional phosphomolybdic polyacid-based nickel coordination polymer and 20 mg of acetylene black evenly, take 3 mg of the ground sample and add it to 125 μL of isopropanol, 10 μL of Nafion solution and 365 μL of water, and ultrasonicate for 2 hours to obtain a uniformly dispersed mixed solution. Take 10 μL of the mixed solution and drop it on the pretreated carbon cloth. After standing at room temperature for 10 hours, the working electrode modified by the chain-type phosphomolybdic polyacid-based nickel coordination polymer was obtained, which was used to test the nitrate reduction performance.